2005
DOI: 10.1242/jcs.02626
|View full text |Cite
|
Sign up to set email alerts
|

Shroom regulates epithelial cell shape via the apical positioning of an actomyosin network

Abstract: The actin-binding protein Shroom is essential for neural tube morphogenesis in multiple vertebrate organisms, indicating its function is evolutionarily conserved. Shroom facilitates neurulation by regulating the morphology of neurepithelial cells. Shroom localizes to the apical tip of adherens junctions of neural ectoderm cells in vivo and to the apical junctional complex (AJC) in MDCK cells. Induced expression of Shroom in polarized epithelia elicits apical constriction and dramatic reorganization of the apic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
341
4
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 241 publications
(374 citation statements)
references
References 38 publications
24
341
4
5
Order By: Relevance
“…A mixture of ZO1(ko)/2(kd) and ZO1(wt)/2(wt) Eph4 cells was cultured and examined by immunofluorescence microscopy ( Figure 1). In fully confluent ZO1(wt)/2(wt) Eph4 cells with linear ZO-1/2 signals at TJs, the linearly arranged signals for E-cadherin/actin/myosin-2 overlapped at the ZA, as shown previously (Bertet et al, 2004;Zallen and Wieschaus, 2004;Hildebrand, 2005). In contrast in confluent ZO1(ko)/2(kd) Eph4 cells, AJs were associated with partially linearized patterns of E-cadherin and actin, but not with myosin-2, a previously unreported AJ state, which we have designated the "prezonula-AJ."…”
Section: Perturbation Of Formation Of Za By Deficiency Of Zo-1/2supporting
confidence: 75%
“…A mixture of ZO1(ko)/2(kd) and ZO1(wt)/2(wt) Eph4 cells was cultured and examined by immunofluorescence microscopy ( Figure 1). In fully confluent ZO1(wt)/2(wt) Eph4 cells with linear ZO-1/2 signals at TJs, the linearly arranged signals for E-cadherin/actin/myosin-2 overlapped at the ZA, as shown previously (Bertet et al, 2004;Zallen and Wieschaus, 2004;Hildebrand, 2005). In contrast in confluent ZO1(ko)/2(kd) Eph4 cells, AJs were associated with partially linearized patterns of E-cadherin and actin, but not with myosin-2, a previously unreported AJ state, which we have designated the "prezonula-AJ."…”
Section: Perturbation Of Formation Of Za By Deficiency Of Zo-1/2supporting
confidence: 75%
“…Results from our lab have shown that Shrm3 is capable of regulating cellular architecture by controlling the distribution of a contractile actomyosin network [Hildebrand, 2005]. Work presented here suggests that Shrm4 may also share this property.…”
Section: Discussionmentioning
confidence: 55%
“…Shrm4 localization is dependent on an intact actin cytoskeleton and appears to be mediated by a novel actin targeting sequence located in the central portion of the protein. Shrm4 distribution is coincident with non-muscle myosin II, suggesting that, like Shrm2 and Shrm3, Shrm4 might regulate cytoskeletal or cellular architecture through a myosin II-dependent pathway [Hildebrand, 2005;Dietz et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations